KINERJA DAN KEPUASAN PETANI TERHADAP PENYULUH PERTANIAN DI KECAMATAN BANDAR MATARAM, KABUPATEN LAMPUNG TENGAH - Abdul Mutolib; Maria Ditha Ayu Suari; M.S Taufiqurrahman; Neng Reza Puji L; Vania Clairine (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2023)
This study aims to identify the performance and satisfaction of farmers with agricultural extension agents. The research was carried out in Sendang Agung Mataram Village, Central Lampung Regency from October to November 2021. The number of respondents was 24 farmers who were taken by accidental sampling method. Data collection used a questionnaire using a Likert scale which was analyzed by interactive data analysis. The results of the research show that the performance of agricultural extension workers as facilitators is quite good. Of the six performance indicators of agricultural extension workers as facilitators, five indicators performed quite well and one indicator received a poor rating. The indicator that received a poor performance rating was the extensionist's support in assisting the preparation of farmer work programs. Overall, farmers are not satisfied with the performance of agricultural extension workers. Indicators that have low satisfaction are: 1) providing training/ services to farmers, 2) evaluating and reporting the results of the implementation of agricultural extension activities and the responsiveness of extension workers in providing problem solutions to farmers.